THE BUSINESS DEVELOPMENT PROSPECTS OF SHRIMP PASTE AT KUALA TUNGKAL COASTAL FISHING PORT OF TANJUNG JABUNG WEST REGENCY JAMBI PROVINCE - Mhd Toariaunaldi; Hendrik '; Hamdi Hamid (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted in March 2017 at Sentra Processing Center ofKuala Tungkal Coastal Fishing Port of Tanjung Jabung West Regency, JambiProvince. This study aims to determine the amount of Cost and Income, marketingflow, business feasibility analysis, and business development prospects of theShrimp paste Business in Tanjung Jabung Barat Regency. The method used in thisresearch is case study method.Shrimp paste business The Sumber Rezeki Group has net income > IDR20,000,000 per month after deducting expenses. Marketing of shrimp paste atFishery Port of Kuala Tungkal is business owner to collecting salesman,collecting salesman to local consumer, direct business owner to local consumer,and business owner directly to outside consumer. The results of feasibilityanalysis obtained a profit of IDR. 23.224.573 per cycle (month) and RCR 1,6,FFR 24%, and PPC 4.1 years. The prospect of shrimp paste shrimp businessdevelopment is good, based on raw material criterion, marketing, and businessanalysis.Keywords: Prospects, Shrimp Paste Business, Tanjung Jabung West Regency